PENERAPAN PRINSIP KEHATI-HATIAN DALAM PEMBERIAN KREDIT DENGAN JAMINAN HIPOTEK KAPAL LAUT PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk KANTOR WILAYAH MANADO - , Dian Samto Indrayana, Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to find out the application of cautiousness principles in giving credit by vessel guarantee on PT. Bank Rakyat Indonesia (Company) Ltd of Manado Regional Office and legal consequences upon the inapplicable cautiousness principles as well. This research is a normativeâempiric legal application, i.e. legal research concerning the implementation of normative legal stipulation on each particular legal event occurs in public. The report of this research is analytical descriptive, meaning that the report explains (describes) field facts using normative analysis